Endogenous group formation in experimental contests - Luisa Herbst; Kai A. Konrad; Florian Morath (Wissenschaftszentrum Berlin für Sozialforschung (WZB), 2013)
We study endogenous group formation in tournaments employing experimental threeplayer contests. We find that players in endogenously formed alliances cope better with the moral hazard problem in groups than players who are forced into an alliance. Also, players who are committed to expending effort above average choose to stand alone. If these players are forced to play in an alliance, they invest even more, whereas their co-players choose lower effort. Anticipation of this exploitation may explain their preference to stand alone. – – Wir untersuchen die endogene Bildung von Gruppen in Wettkämpfen in experimentellen Drei-Spieler-Wettbewerben. Es zeigt sich, dass Spieler in endogen gebildeten Allianzen besser mit dem Moral Hazard-Problem in Gruppen zurechtkommen als Spieler, die in eine Allianz gezwungen werden. Außerdem entscheiden sich Spieler, die bereit sind, überdurchschnittlichen Einsatz zu leisten, allein zu agieren. Sind diese Spieler gezwungen in einer Allianz zu spielen, investieren sie sogar mehr, wogegen ihre Mitspieler ihren Einsatz reduzieren. Die Erwartung dieser Ausbeutung ist eine mögliche Erklärung für ihre Präferenz allein zu agieren.
Keywords: D72; D74; 330; endogenous group formation; contest; conflict; alliance; experiment; moral hazard problem; free-riding; in-group favoritis